Hypersensitivity to nonsteroidal anti-inflammatory drugs: From pathogenesis to clinical practice - Mota,Inês (2018)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are one of the leading causes of hypersensitivity reactions, which affect a considerable percentage of the general population. These drugs can induce a wide spectrum of reactions with distinct timing, organ involvement and severity, including either immunological or nonimmunological mechanisms. A proper diagnosis can be particularly challenging since most reactions result from the pharmacological mechanism of the drug and might be dose - dependent. The clinical classification of NSAIDs - induced reactions has changed over time. Accurate diagnosis depends on strict clinical history and proper understanding of underlying mechanism. Skin testing and in vitro testing have limited usefulness. Drug challenge tests with the culprit or alternative drugs are the gold standard for the diagnosis, and provide information about drug avoidance and safe therapeutic options. In selected cases drug desensitization might be a therapeutic option. In this review, we will attempt to highlight the main aspects to be taken into account for a proper management of patients with NSAIDs hypersensitivity.